Knowledge and practice towards care and maintenance of peripheral intravenous cannula among nurses in Chitwan Medical College Teaching Hospital, Nepal - Chadani Osti; Menuka Khadka; Deepa Wosti; Ganga Gurung; Qinghua Zhao (Wiley, 2019)
Abstract Aim The study is mainly concerned about the care and maintenance of peripheral intravenous cannulation: to determine the knowledge and practice of nurses towards care and maintenance of IV cannula and to find out the obstacles encountered in caring and maintaining IV cannula. Intravenous cannulation is a common procedure performed by nurses in every hospital and closely associated with the risk of nosocomial infections if standard care is not provided. Design A descriptive cross‐sectional study design was carried out. Methods Nurses' knowledge and practice towards care and maintenance of peripheral intravenous cannula were assessed using a validated semi‐structured self‐administered questionnaire through the census method. Data were analysed through SPSS program. The comparison was done between knowledge and practice. Results The findings revealed that 84.72% respondents were doing correct practices despite the fact that only 82.47% respondents had proper knowledge. Most nurses have good knowledge of caring and maintaining peripheral intravenous cannulation but there were some without proper knowledge and practice. This could be a potential risk factor for patient safety.